A acidificação de dejetos líquidos de suínos afeta as emissões de amônia e gases de efeito estufa no processo de compostagem automatizada - Doneda, Alexandre (2014)
Composting of pig slurry (DLS) is an important strategy to mitigate the environmental damage of intensive pig farms. Despite being a promising strategy, one of the problems from composting is still the losses of nitrogen (N) by volatilization of ammonia (NH3). Acidification of DLS before to addition to the piles, reducing the pH and thus, the piles, may be a possibility to circumvent this problem. However, little is known about the effect of acidification of DLS, not only on emissions of (NH3) as with respect to emissions of greenhouse gases (GEE) (CO2, CH4 e N2O) during the process, especially in automated systems where the addition of manure and mixing of piles are frequent. This study was conducted with the objective of evaluating the effect of acidification of pig slurry on ammonia and greenhouse gases emissions during an automated composting process. The study was conducted at the Federal University of Santa Maria, RS, during 154 days in compost piles containing the mixture of wood shavings and sawdust as substrate, with weekly additions of DLS, followed by two revolving piles during the first 106 days. Between 107 and 154 days were made only weekly turnings piles. Two treatments were tested, one with manure acidification with H3PO4 to pH around 6.0 and another without acidification. The evaluation of emissions of NH3 was carried out in semi-open static chambers, while the GEE was performed in static chambers. The pH of DLS was reduced on average 0.87 units with acidification compared to the original values and the average value of all applications was 5.84. In compost piles, the pH decreased from 8.11 to 6.72 on average during all period of the experiment. The concentrations of NH4+ at the end of the experiment were, on an average of two evaluated layers, 102.98 mg kg-1 in the pile without acidification and 398.81 mg kg-1 in the pile with acidification, while the levels of NO3- were 13.37 mg kg-1 in the pile without acidification and 1371.04 mg kg-1 in the pile with acidification. The cumulative emission of NH3 in the treatment with acidification was 32.6 g m-2, 70% lower than the treatment without acidification (107.8 g m-2). Acidification of DLS also reduced the cumulative CO2 emissions to the atmosphere of 91.65 kg m-2 to 69.05 kg m-2 (25%) and the CH4 of 639.97 g m-2 to 227.13 g m-2 (65%). On the other hand, acidification of DLS at the time of addition to the substrate increased the cumulative emission of N2O by 30.4 g N-N2O m-2 (130%) at 154 days of composting.